Better Privacy and Security in E-Commerce: Using Elliptic Curve-Based Zero-Knowledge Proofs - Almuhammadi, Sultan (2004)
We propose an approach using elliptic curve-based zero-knowledge proofs in e-commerce applications. We demonstrate that using elliptic curved-based zero-knowledge proofs provide privacy and more security than other existing techniques. The improvement of security is due to the complexity of solving the discrete logarithm problem over elliptic curves.